A Study of the Turning Point of China's Debt - Zhu, Xiaohuang (Springer Singapore, 2018)
This book proposes a method for calculating China's debt based on a quantitative econometric analysis. This is conducted by measuring the relationship between China's debt size and economic growth. The conclusion that is reached is as follows: China's current debt has already exceeded the inflection point, and that means that it is now having an adverse effect on its economic performance. The book also focuses on China's debt problems as a whole, highlighting debt issues faced by different entities and industries, as well as the ratio and structure of the virtual and real economies. The contents are presented in three major principles: theory, oriented,data, and oriented policy. .